Strategi Program Pemuliaan Tanaman Kelapa Sawit (Elaeis guinensis Jacq.) pada Lahan Suboptimal di PT Binasawit Makmur - Muhammad Antony Jefri Pratama; Nurcahyono Indarto; Fahmi Wendra; Victor Manotar Pademan Manalu; Agry Widya Pradipta; Bayu Lesmana; Upit Sarimana; Pratiwi Erika; Zulhermana Sembiring; Dwi Asmono (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Pratama et al, 2018. Oil Palm Breeding Program Strategy for Suboptimal Area in PT Binasawit Makmur . JLSO 7(1):26-36. Suboptimal areas have great potential to be used an alternative land for cultivation of oil palm.We needed superior oil palm material to be able to grow well on that land. PT. Binasawit Makmur (BSM) through the Breeding Unit has developed a strategy regarding the assembly of superior material oil palm drought resistant. Therefore, this research aimed to develop a strategy regarding breeding program in suboptimal lands of PT Binasawit Makmur. The strategies used were introducing, evaluating, and selecting genetic material based on productivity components (total and weight of fresh fruit bunches/ha, extraction rate) and high increment. In addition, the efforts have been made to obtain drought tolerant material are conducting a progeny trial (DXP Trial) on mature palm to obtain drought tolerant in the dried season. Based on the results of the progeny trial, both of parents were traced to a crossing program. Currently, the seeds of the crossing have been obtained to confirm the results of the research on the nursery scale. In the nursery trial, research will be conducted to measure the proline content, stomata and chlorophyll content. Selection in the mature palm DXP progeny trial was followed by application a molecular tool such as SSR and SNP. Through this approach, a superior genetic material in terms of productivity and also drought tolerance can be developed and therefore can be used for recombination and release of new varieties.